Improving warehouse efficiency through effective inventory management practices / Aidil Hanafi Amirrudin ... [et al.] - Amirrudin, Aidil Hanafi; Kamaruddin, Nur Syuhadah; Salehuddin, Nurshahirah; Ibrahim, Suraiya (Research Management Institute (RMI), 2023)
Several business establishments have used inventory management strategies to strike a balance between responsiveness and efficiency. This study's primary objective was to assess the effect of inventory management practices on the warehouse efficiency of supermarkets and retail stores in Kedah and Perlis, specifically supermarkets. This study utilises a quantitative method by using primary data from questionnaires and secondary data compiled from prior studies' results. Statistical Packages for the Social Science (SPSS) version 25 software was used to analyse the data. The relationship between the independent and dependent variables was determined using regression analysis. The outcome showed that the inventory reorders point and supplier partnership management variable were accepted. However, the information technology hypothesis was rejected. This study recommends that supermarkets and retail stores utilise the best inventory management strategies to increase warehouse efficiency. It enables the tracking of stock unit movement in the warehouse, facilitates stock counting in the warehouse, maximises the use of available warehouse space, improves inventory data accuracy, reduces inventory theft, and enhances inventory cycle counting.